THE DISPUTES RESOLUTION AGAINST PARTIES OF DIFFERENT CITIZENSHIP - Annie Myranika (Jurnal Pembaharuan Hukum, 2023)
The agreement is carried out by the agreement of both parties which has binding legal consequences and is valid according to law, if the parties do not comply with or violate the provisions agreed upon by both parties, a default arises. The issue that will be raised in this research is the settlement of evidence against default cases in court with parties of different nationalities based on judges' considerations in deciding default cases between parties of different nationalities, and the legal consequences of these defaults. This study aims to identify and analyze the settlement of defaults on differences in citizenship status from the perspective of international private law and the legal consequences of default. This research approach method uses qualitative research with primary data materials and secondary data materials which are analyzed using literature studies and normative juridical approaches that refer to applicable law.